Political sentiment analysis of tweets before and after the Greek elections of May 2012. (1st January 2013) - Kermanidis, Katia Lida; Maragoudakis, Manolis
Political sentiment analysis using social media content has attracted significant interest in the last years. The present work utilises limited linguistic resources in a knowledge-poor approach to political sentiment identification from Greek tweets, posted a few days before and a few days after the Greek parliamentary elections of May 6th, 2012. Rather than the accurate prediction of the election results, the main focus of the proposed work is the investigation of the alignment between web and actual political sentiment in a bi-directional manner: the impact/reflection of the tweets' sentiment on the elections as well as the impact of the elections' results on web sentiment, and its shift around such a major political event.